The Comparative Analysis of Financial Performance of Sharia Banking in Indonesia - Ahmad Syarief Iskandar; Muhammad Ikram. S; Hindun Musalamah; Ilham Ilham (Universitas Negeri Makassar, 2021)
The objective of this research was to determine the level of bank finance Muamalat, Bank Syariah Mandiri, and Bank BNI Syariah on the solvency ratio of Capital Asset Ratio (CAR), earning assets quality ratio of Non-Performing Financing (NPF), profitability ratio of Return On Assets (ROA), and liquidity ratio of Financing too Deposite Ratio (FDR). Also, to find out and prove empirically about differences in financial performance at Bank Muamalat Indonesia, Bank Syariah Mandiri, and Bank BNI Syariah during the 2015-2019 period. The method used in this research was a quantitative method using statistical techniques in the Kolmogorov Smirnov test and one-way ANOVA parametric test. First, the data processed was secondary in the form of bank financial reports for 2015-2019 taken from the database of Bank Muamalat, Bank Syariah Mandiri, and Bank BNI Syariah. Then the data was converted into IBM SPSS statistics 24 for windows. The statistical tests show significant differences in financial performance between Bank Muamalat, Bank Syariah Mandiri, and Bank BNI Syariah based on the CAR and ROA ratios. At the same time, for NPF and FDR, there is no significant difference. Therefore, the financial performance of Bank BNI Syariah is better in terms of CAR solvency ratio, earning assets quality ratio NPF, and ROA profitability ratio, while in terms of FDR liquidity ratio, Bank Muamalat's performance is better.